Abundance Of Soil Fauna In Beneng Taro (Xanthosoma undipes K. Koch) AT Various Altitudes - Saputra, Agis; Hermita, Nuniek; Sulistyorini, Endang; Utama, Putra (Jurnal Agroekoteknologi Terapan, 2026)
Beneng Taro (Xanthosoma undipes K. Koch) is a local food crop from Gunung Karang, Banten, with high nutritional potential whose productivity is closely related to soil biological conditions. This study evaluated soil fauna abundance and diversity in talas beneng cultivation areas across three elevations: highland (851-858 m asl), midland (590-602 m asl), and lowland (343 m asl). A quantitative exploratory approach was applied using pitfall traps with ten replications per site and composite soil sampling at 0-20 cm depth. Soil chemical properties (pH, C-organic, N-total, and C/N ratio) were analyzed, and diversity was calculated using the Shannon-Wiener index. A total of seven soil fauna orders were recorded, with Hymenoptera dominating all sites. The midland exhibited the highest abundance (67 individuals), while the lowland showed the highest diversity index (H’=1.077 medium category). Variations in abundance and diversity were associated with differences in soil pH, nitrogen availability, and C/N ratio, which influenced decomposition rates and nutrient dynamics. The findings indicate that elevation-related environmental factors significantly shape soil fauna communities and underscore the importance of soil fertility management in supporting sustainable talas beneng cultivation. Keywords: Abundace, Altitude, Beneng taro, Soil Chemical Properties, Soil Fauna.